Health-related quality-of-life, work productivity, and economic burden among patients with Parkinson's disease in Japan. (2nd December 2018) - Yamabe, Kaoru; Liebert, Ryan; Flores, Natalia; Pashos, Chris
Abstract: Aims: This study aimed to characterize the burden of Parkinson's disease (PD) by examining health-related quality-of-life (HRQoL), impairments to work productivity and daily activities, healthcare resource use, and associated costs among Japanese patients with PD. Materials and methods: This retrospective cross-sectional study used data from the 2009–2014 Japan National Health and Wellness Survey (NHWS) ( n  = 144, 692). HRQoL (Short Form 36-Item Health Survey version 2), impairments to work productivity and daily activities (Work Productivity and Activity Impairment Questionnaire), healthcare resource utilization, and annual costs were compared between respondents with PD ( n  = 133) and controls without PD ( n  = 144, 559). The effect of PD on outcomes was estimated using propensity score weighting and multivariable regression models. Results: HRQoL was lower in patients with PD compared to the control group, with reduced physical (41.3 vs 51.3) and mental (35.7 vs 45.4) component summary scores and health state utility scores (0.62 vs 0.77; p  < .001 for all). Patients with PD also reported higher levels of absenteeism (19.3% vs 3.3%), presenteeism (45.2% vs 18.5%), overall work impairment (52.8% vs 20.3%), and activity impairment (49.6% vs 20.8%) than controls without PD ( p  < .001 for all). In addition, patients with PD had higher healthcare resource utilization, direct (¥3, 856, 921/$37, 994 vs ¥715, 289/$7, 046), and indirect (¥2, 573, 938/$25, 356 vs ¥902, 534/$8, 891) costs compared with controls without PD ( p  < .001 for both). Limitations: Data were cross-sectional and did not allow for causal inferences. Although the NHWS demographically represents the Japanese adult population, it is unclear whether it adequately represents the adult population with PD in Japan. Conclusions: PD was associated with poorer HRQoL, greater work productivity loss, and higher direct and indirect costs. The findings suggest that an unmet need exists among patients with PD in Japan. Improving PD treatment and management could benefit both patients and society.